PENGEMBANGAN ELEKTRONIK MADING BERBASIS WEB DENGAN FITUR MULTIUSER - , TAKDIR HARI MUKTI ([Yogyakarta] : Universitas Gadjah Mada, 2014)
The growth of information are very high and balanced of computerized sistem development. Information submission requires internal participants, external and intermediary between both of them. A new breakthrough is required to make the wall magazine more attractive, organized, accesible and manageable. Mass communication medias using interactive tools cause a flow of information that allow users receive informations at the same time. Web based electronic wall magazine development is interactive media to support and facilitate communication society. It has main features such as information management, air time management, history management, conduct pin feature and perform like feature. Web based electronic wall magazine is designed using use case diagram, activity diagrams and class diagram. Model-View-Controller concept based on Object Oriented Programming, PHP programming language, Yii framework and MySQL database is used to build electronic wall magazine. Electronic wall magazine provides services such as electronic information wall magazine's user management with a multiuser bulletin board and information of air time duration configuration that is equipped with pin feature and like feature on any displayed information. Electronic wall offers facilities such as magazine are sharing information between all users by conducting pin feature and interactive interface.